A study on factors influencing undergraduate students’ career decision / Muhammad Hafiz Aziz - Aziz, Muhammad Hafiz (Faculty of Business and Management, 2018)
The purpose of this study is to investigate factors influencing undergraduate students’ career decision. The independent variables are extrinsic factors, intrinsic factors and interpersonal factors while the dependent variable is career decision. The study was conducted towards part six students of Faculty of Business and Management in Universiti Teknologi Mara (UiTM) Cawangan Melaka Kampus Bandaraya. Sample technique used was stratified random sampling whereby the students are group based on their program enrolled in university and 59% of the students from each programs picked as sample of study. The sample size is 181 respondents out of 307 of total population. Pearson’s correlation analysis was conducted to analyze the relationship between extrinsic factors, intrinsic factors and interpersonal factors with career decision. The result showed that all variable have a positive correlation since the “p” value is at significant level which is lower than 0.001. Hypothesis also tested using Pearson’s correlation analysis. The result showed that all hypothesis are accepted since all variable are significant. Multiple regression analysis was used to determine the most dominant factors that influence career decision. It showed that all variables are contributed 28% towards career decision and intrinsic factors is the dominant factors that influence career decision since the Beta (β) value is the highest which is 0.275.